Polskie przekłady zbioru Priče iz davnine Ivany Brlić Mažuranić - Gostomska, Anita (Przekłady Literatur Słowiańskich, 2016)
Polish translations of Croatian tales of long ago by Ivana Brlić‑Mažuranić Despite the over one hundred years long popularity of Ivana Brlić‑Mažuranić in Croatia, her collection Croatian Tales of Long Ago remains almost absent in Poland. An attempt to determine the reasons for this absence involves the reconstruction of the circumstances of its Polish translations and the outline of the translators’ silhouettes, which leads to Wanda Pogonowska, who was a visual artist and a painter by education and who should be considered as the first Polish translator of the famous Croatian tales. Although she took on the translation twice (in the 1930s and 1950s) and has remained the only person who translated the entire collection into Polish, the final effect of her translation efforts, due to the problems with its publication, is still unknown, and the memory of Wanda Pogonowska is slowly fading away. Wiktor Bazielich was also an amateur translator but who made up for his lack of professionalism with his extraordinary perseverance and managed to publish in the interwar press his own translation of one fairy tale from the Brlić‑Mažuranić’ collection. The same tale about the fisherman Palunko was translated again forty years later by Magdalena Petryńska (unaware of the existence of the earlier Polish version), who, with her considerable achievements, in contrast to the pre‑war translators of Brlić‑Mažuranić, proudly represents the circle of the most outstanding contemporary Polish translators of South Slavic prose. Existing translations show that the translators adopted extremely different translation strategies. Wiktor Bazielich’s attitude, which could result from his intention of introducing Polish recipients to the realities of South Slavic culture or from the translator’s skills, is close to formal equivalence; while the procedure of Magdalena Petryńska was dictated by a concern for the communication comfort of the story’s recipients — children and can be described as functional equivalence. Key words: Ivana Brlić‑Mažuranić, Croatian Tales of Long Aago, Wanda Pogonowska, Wiktor Bazielich, Magdalena Petryńska, translation